2022
DOI: 10.1038/s41598-021-04176-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of plasma biomarkers for diagnosis of breast cancer in South Asian women

Abstract: Breast cancer is the most common malignancy among women globally. Development of a reliable plasma biomarker panel might serve as a non-invasive and cost-effective means for population-based screening of the disease. Transcriptomic profiling of breast tumour, paired normal and apparently normal tissues, followed by validation of the shortlisted genes using TaqMan® Low density arrays and Quantitative real-time PCR was performed in South Asian women. Fifteen candidate protein markers and 3 candidate epigenetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Consistently, the methylation level is associated with breast cancer prognosis and hence, can be used as a diagnostic marker (Xiao et al, 2018). Moreover, multivariate diagnostic analysis of the methylation status of WIF1, Sostdc1, and DACT2 showed up to 91% specificity and 100% sensitivity in discriminating breast cancer (invasive and non-invasive) from benign tumours and controls and may be a complementary tool for breast cancer diagnosis (Rajkumar et al, 2022). A gastric cancer study found that Sostdc1 expression is modulated by epigenetic mechanisms and its downregulation may be caused by promoter hypermethylation (a potential prognostic factor) and tumour suppression, with the expression of…”
Section: Sostdc1 Methylation Inhibits Cancer Developmentmentioning
confidence: 83%
See 3 more Smart Citations
“…Consistently, the methylation level is associated with breast cancer prognosis and hence, can be used as a diagnostic marker (Xiao et al, 2018). Moreover, multivariate diagnostic analysis of the methylation status of WIF1, Sostdc1, and DACT2 showed up to 91% specificity and 100% sensitivity in discriminating breast cancer (invasive and non-invasive) from benign tumours and controls and may be a complementary tool for breast cancer diagnosis (Rajkumar et al, 2022). A gastric cancer study found that Sostdc1 expression is modulated by epigenetic mechanisms and its downregulation may be caused by promoter hypermethylation (a potential prognostic factor) and tumour suppression, with the expression of…”
Section: Sostdc1 Methylation Inhibits Cancer Developmentmentioning
confidence: 83%
“…Sostdc1 is involved in the progression and development of multiple cancer types, including breast, gastric, renal, bladder, and thyroid cancers (Blish et al, 2008;Gopal et al, 2013;Rawat et al, 2014;Li et al, 2020). Sostdc1 deficiency is associated with larger tumour sizes (Clausen et al, 2011).…”
Section: Role Of Sostdc1 In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Complement factor D (CFD) cleaves factor B when the latter is complexed with factor C3b, activating the C3bbb complex, which then becomes the C3 convertase of the alternate pathway. The levels of CFD (plasma and tissue) were significantly downregulated in patients with ductal carcinoma in-situ (DCIS) and invasive BC when compared to controls [118]. Its precursor polypeptide chain has 253 AA, where AA 1-20 -the signal peptide, AA21-25 -propeptide, AA 26-253complement factor D (Mw: 6.85/24405).…”
Section: Complement Factor D (Cfad_human)mentioning
confidence: 99%